Hubungan Sosiodemografi dan Penyakit Penyerta Terhadap Nilai D-Dimer Pasien Covid-19 - Michael, Michael; Ramatillah, Diana Laila; Hartuti, Silvy (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
D-dimer is a degradation of soluble fibrin which is the result of systematic degradation of vascular thrombus through a fibrinolytic mechanism. The purpose of this study was to look at sociodemographic factors and other diseases that affect the d-dimer value of COVID-19 patients. This study uses a retrospective cohort method with the collection of sampling is convenience sampling. There were 137 patients who met the study criteria. Age, BMI, blood pressure and respiration rate are sociodemographics that affect the D-dimer lab value. For comorbidities that affect the D-dimer lab value, there are CKD, anemia, hypertension and heart disease. A high D-dimer value also has a significant relationship with the severity of the COVID-19 infection. In addition, patients who died were found to have high D-dimer values. By this research, patients with high age, BMI, blood pressure and respiration rate can increase patient mortality and for comorbidities that have an important role in increasing mortality in Covid-19 patients are CKD, anemia, hypertension and heart disease.